Hyperbola Style In Nizar Qabbani “Asyhadu An Lā Imraata Illa Anti” : Hyperbola Style In Nizar Qabbani “Asyhadu An Lā Imraata Illa Anti” - mawarida, Hanim (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
This study discusses the problem of the language style used in the poem "Asyhadu An Lᾱ Imraata Illa Anti" by Nizar Qabbani. This study aims to describe the form of words in a poem entitled "Asyhadu An Lᾱ Imraata Illa Anti" by Nizar Qabbani, which has several language styles, especially hyperbolic language styles. This research uses descriptive qualitative analysis methods. Data analysis is carried out through several stages, namely literature studies by reading, recording, and identifying on the lines of poems that contain language styles. The results of this study show that the author uses several forms and types of hyperbolic language styles in his poems. The hyperbolic stylistics are known in the use of verbs, nouns, and adjectives of its stanzas. Moreover, there are also found several pusi stanzas expressed with quantitative hyperbolic language styles and qualitative hyperbolic language styles.